RETRACTED: Kesesuaian Fiqih Talak Syi’ah Imamiyyah dengan Aturan Perkawinan Di Indonesia - Thoriq Ulumuddin; M. Habibi (Muqaranah, 2022)
Abstract: One of Laws of Marriage in Indonesia is regulated by Presidential Instruction No.1 in 1991 regarding Islamic Law Compilation (KHI) where it does not fully agree with opinions of the scholar (‘Ulama) of Madzhab al-Arba'ah Sunni as contained in articles 115, 129, 130 and 134 because these articles have never been found in view of Madzhab al -Arba'ah Sunni and even tends to be counter. Therefore, many religious institutions or Islamic organizations have issued "fatwa" regarding the fall of divorce outside Court. This has led to the need for new efforts to explore Law of Divorce outside Madzhab al-Arba'ah Sunni. The study aims to determine how concept of Fiqh Talak Syi'ah Imamiyyah, concept of Talak in Islamic Law Compilation, and its relevance to rules of marriage. This research is a qualitative research using a statutory approach or a juridical approach and a comparative approach with the library research method. The results showed that there were similarities and differences. similarities such as from the political aspect, the aspect of making it difficult for divorce, the aspect of the fall of divorce and witnessing in the divorce. while differences such as from the aspect of taking legal sources and differences in defining divorce. so that the validity of divorce in the Indonesian marriage law and its practice in court is beyond doubt..